2003
DOI: 10.1001/archderm.139.5.607
|View full text |Cite
|
Sign up to set email alerts
|

Dermatologist Detection and Skin Self-examination Are Associated With Thinner Melanomas

Abstract: To investigate patterns of detection and variables associated with early diagnosis of melanoma in a population at intermediate melanoma risk.Design: Survey.Setting: Hospital and university centers belonging to the Italian Multidisciplinary Group on Melanoma.Patients: Eight hundred sixteen patients who were consecutively diagnosed as having melanoma and treated at 11 participating centers.Main Outcome Measure: Relationship between patterns of detection and patient's and physician's delay with melanoma thickness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
106
2
5

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(124 citation statements)
references
References 19 publications
11
106
2
5
Order By: Relevance
“…This criteria required examination "always" or "almost always" of each of eight skin areas (arms and face, chest and front of legs, side of body, back of legs, upper back and tops of shoulders, sides of legs and bottoms of feet, middle and lower parts of back, and back of thighs), except one, which could be examined at least "sometimes" (14). Carli et al showed that 45.8% of their subjects in an Italian cohort reported performing SSE (20.4% regularly and 25.4% occasionally), although SSE criteria were not defined and were determined by the individual patients themselves (13). In an Australian telephone survey of 3,110 residents, Aitken et al defined SSE as having "deliberately checked the skin on your whole body," including "skin front and back," and found that only 25.9% of participants had performed SSE within the last year (10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This criteria required examination "always" or "almost always" of each of eight skin areas (arms and face, chest and front of legs, side of body, back of legs, upper back and tops of shoulders, sides of legs and bottoms of feet, middle and lower parts of back, and back of thighs), except one, which could be examined at least "sometimes" (14). Carli et al showed that 45.8% of their subjects in an Italian cohort reported performing SSE (20.4% regularly and 25.4% occasionally), although SSE criteria were not defined and were determined by the individual patients themselves (13). In an Australian telephone survey of 3,110 residents, Aitken et al defined SSE as having "deliberately checked the skin on your whole body," including "skin front and back," and found that only 25.9% of participants had performed SSE within the last year (10).…”
Section: Discussionmentioning
confidence: 99%
“…In 1996, Berwick et al reported that SSE could reduce melanoma mortality by as much as 63% (12). A 2003 study found that regular performance of SSE was associated with a significantly reduced likelihood of having tumors >1 mm thick at diagnosis [covariate-adjusted odds ratio (OR), 0.65; 95% confidence interval (95% CI), 0.45-0.93], although details regarding the thoroughness and frequency of SSE were not obtained (13). Improved understanding of the effectiveness of SSE has been hampered by variable study definitions of SSE, including the number or percent of body sites examined and the frequency and method of examination (14)(15)(16)(17) and the small number of studies examining the reported benefits of techniques to supplement SSE, such as the use of photographs (8,18,19).…”
Section: Introductionmentioning
confidence: 99%
“…Skin screening examinations by medical professionals result in the identification of thinner melanomas (28,29). It is also well established that the majority of melanomas are detected by the patients or their spouses (28,30,31).…”
Section: Introductionmentioning
confidence: 99%
“…2 Guidelines highlight the role of general practitioners in prevention, 3 including primary prevention by counseling on sun exposure 4,5 and secondary prevention by regularly performing a total skin examination and encouraging self-examination. 3,6 Self-examination has been shown to improve the probability of early diagnosis 7 and may reduce melanoma-related mortality by 63%. 8 In more than one-half of cases of melanoma, patients may be the first to identify the lesion 7,9 ; however, less than 25% of patients perform skin self-examination.…”
Section: Introductionmentioning
confidence: 99%
“…3,6 Self-examination has been shown to improve the probability of early diagnosis 7 and may reduce melanoma-related mortality by 63%. 8 In more than one-half of cases of melanoma, patients may be the first to identify the lesion 7,9 ; however, less than 25% of patients perform skin self-examination. 10 There have been many advertising campaigns worldwide on melanoma prevention, but their effectiveness in modifying patient behavior is difficult to measure.…”
Section: Introductionmentioning
confidence: 99%